Computational tools for fluid power system design: towards distributed AI and virtual reality. (1st January 2000) - Xiang, W.; Fok, S.C.; Yap, F.F.
The paper provides an overview of research and development activities in the field of computational technologies for fluid power system design. It aims to identify key concepts and their applications for the development of the next generation of design tools for fluid power system design. Some of the drawbacks in the contemporary procedure for fluid power system design are presented. A new DAI-virtual prototyping approach for fluid power system design is proposed in this paper.